Indonesia's institutional strategy in RCEP: analyzing economic liberalism and ASEAN centrality through neoliberal institutionalism - Muhammad Ridha Iswardhana (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This research examines Indonesia’s participation in the Regional Comprehensive Economic Partnership (RCEP), the world’s largest regional trade agreement, focusing on the tension between Indonesia’s national economic interests and ASEAN’s principles of economic integration. The study addresses critical gap in literature by analyzing tension between Indonesia's national economic interests and ASEAN’s economic integration principles, particularly considering debates over ASEAN centrality and the role of institutional neoliberalism in regional governance. Using these frameworks, along with economic liberalism, this study analyzes Indonesia navigates its role within RCEP. The research employs a qualitative case study approach, analyzing policy documents and institutional reports through theoretical triangulation. Findings indicate that Indonesia’s participation in RCEP is not only a commitment to economic liberalism but also a strategic effort to strengthen ASEAN centrality through institutional mechanisms that regulate trade and foster regional cooperation. This study contributes to the literature by conceptualizing RCEP as a crucial institutional tool in ASEAN’s economic integration. It offers new insights into Indonesia can simultaneously pursue national interests and contribute to regional integration within a structured institutional framework. The research advances theoretical understanding by integrating neoliberal institutionalism, economic liberalism, and ASEAN centrality to interpret Indonesia’s role in regional economic governance.